Single-route synthesis of magnetic biochar from sugarcane bagasse by microwave-assisted pyrolysis - Mohamed Noor, Noraini; Abdullah, Ezzat Chan; Othman, Raihan; Mujawar, Mubarak N. (2016)
This study investigated a novel method of preparing magnetic biochar from sugarcane bagasse by microwave-assisted pyrolysis at a microwave power of 600W. The samples were characterized by several methods such as scanning electron microscopy (SEM), X-ray diffraction (XRD), flame atomic absorption spectroscopy (FAAS), vibrating sample magnetometer (VSM), and FTIR. The effects of the radiation time were investigated. The optimum conditions for producing high yield 69% magnetic biochar from sugarcane bagasse by microwave heating were 30 min of radiation time and an impregnation ratio (Fe2O3:biomass) of 0.45. The magnetic biochar produced enhanced the route for the removal of 96.17% of hazardous Cadmium (Cd2+) from aqueous solutions.